2019
DOI: 10.1152/ajprenal.00395.2019
|View full text |Cite
|
Sign up to set email alerts
|

Knockout ofP2rx7purinergic receptor attenuates cyst growth in a rat model of ARPKD

Abstract: The severity of polycystic kidney diseases (PKD) depends on the counterbalancing of genetic predisposition and environmental factors exerting permissive or protective influence on cyst development. One poorly characterized phenomenon in the cystic epithelium is abnormal purinergic signaling. Earlier experimental studies revealed the high importance of the ionotropic P2X receptors (particularly, P2X7) in the pathophysiology of the cyst wall. To study mechanisms of P2X7 involvement in cyst growth and aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…In contrast, Aurkb protein expression level in Aurkb ER Cre/+ heterozygous mice was quite similar to their wildtype controls (Figure 3D). This is consistent with other reports that heterozygous knockout mice can express similar or more than half of the proteins relative to wildtype control mice in the target genes (Gineste et al, 2013;Zhou et al, 2015;Arkhipov et al, 2019). It is reported that an Aurkb knockout mouse in which exons 2-6 were excised is embryonic lethal, older Aurkb heterozygous mice approximately 12-24 months of age show decreased survival due to susceptibility for tumorigenesis, and a fraction of Aurkb heterozygous males suffer from oligospermia by 12 months of age (Fernandez-Miranda et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Aurkb protein expression level in Aurkb ER Cre/+ heterozygous mice was quite similar to their wildtype controls (Figure 3D). This is consistent with other reports that heterozygous knockout mice can express similar or more than half of the proteins relative to wildtype control mice in the target genes (Gineste et al, 2013;Zhou et al, 2015;Arkhipov et al, 2019). It is reported that an Aurkb knockout mouse in which exons 2-6 were excised is embryonic lethal, older Aurkb heterozygous mice approximately 12-24 months of age show decreased survival due to susceptibility for tumorigenesis, and a fraction of Aurkb heterozygous males suffer from oligospermia by 12 months of age (Fernandez-Miranda et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our experiments in both T1D and T2D podocytes with specific inhibitors provide compelling evidence that P2X 4 and P2X 7 receptors play a major role in ATP-induced [Ca 2+ ] i levels in diabetic podocytes. Previous research has established that P2X 7 receptor expression increases are linked to PKD, glomerulonephritis, human lupus nephritis, and hypertension-associated renal injury ( Arkhipov et al., 2019 ; Hillman et al., 2005 ; Pereira et al., 2020 ; Vallon et al., 2020 ). In addition, the upregulation of glomerular P2X 7 receptor mRNA and protein expression has been reported in STZ-induced diabetic and ren-2 transgenic hypertensive rat models, and was associated with inflammatory cytokine release and cell death ( Vonend et al., 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies suggest that purinergic signaling is an important contributor to various physiological and pathophysiological processes in the kidney, including diabetes ( Vallon et al., 2020 ). For example, ionotropic P2X 7 receptors are implicated in cyst formation in polycystic kidney disease and also renal interstitial inflammation associated with different kidney pathologies ( Arkhipov et al., 2019 ; Chang et al., 2011 ; Goncalves et al., 2006 ; Taylor et al., 2009a ). Renal proximal tubular P2X 4 activation promotes tubular inflammation and exacerbates ischemic acute kidney injury ( Han et al., 2020 ), and deficient metabotropic P2Y 2 signaling has been shown to aggravate the progression of chronic kidney disease in mice ( Potthoff et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional PC1 also critically affects the transcriptome of kidney cells . In addition, increased expression of pannexin‐1 in cyst lining cells of a mouse and rat PKD model has recently been reported . Under given stimuli (eg, mechanic stimulation, intracellular concentrations of certain ions, etc), higher pannexin‐1 expression may result in higher transport activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings unequivocally indicate the contribution of pannexin‐1 to cyst growth and suggest this channel as druggable target for PKD therapy. Interestingly, pannexin‐1 expression levels appear to be dramatically increased in pathological conditions compared to the healthy kidney making it an especially interesting therapeutic target . BB‐FCF, is considered safe to use.…”
Section: Discussionmentioning
confidence: 99%